Comparison of MELD and Child- Pugh Score for the Prediction of Survival in Portal Hypertension Undergoing Transjugular Intrahepatic Portosystemic Shunt - Liu Kai; Wang Shikai; Wu Xingjiang; Fan Xinxin; He Changsheng; Li Jieshou (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
Objectives: Recently, the model for End-Stage Liver Disease (MELD) was proposed for the prediction of survival in transjugular intrahepatic portosystemic shunt (TIPS) patients. We therefore compared the prognostic accuracy of the MELD model and the Child-Pugh score, in an unselected cohort of TIPS patients followed long-term. Methods: A retrospective chart review and statistical analyses were done on 120 patients consecutively admitted for portal hypertension from 2009 to 2013 in the Jinling hospital (Nanjing, China). Results: The survival rate for all patients was 95.8% at 3 months, 90% at 1 year, and 85.8% at 3 years. Significantly lower survival rates were found in patients with MELD scores of 15 or more in comparison to those with MELD scores of 15 or less (p<0.001).There was no significant difference in survival rate between patients with Child-Pugh classifi cation A and those with Child-Pugh classifi cation B, while the patients with Child-Pugh classification C has a signifi cantly lower survival rate than those with Child-Pugh classification A and B (p<0.001). The discrimination powers of MELD (c statistics: 0.772, 0.680, 0.647 for 3-month, 1-year, and 3-year survival) were not signifi cantly different from the discrimination powers of Child-Pugh score at the same time points (c statistics: 0.795, 0.732, 0.678).